ANALISA PENGARUH PROSES DIGITAL PROOF TERHADAP KUALITAS CETAKAN PADA KEMASAN PRODUK POCKY CHOCOLATE - Kevin Putra Damiana (Kreator, 2026)
Digital proofing plays an important role in ensuring print quality before entering mass production. This study aims to analyze the effect of digital proof on the print quality of Pocky Chocolate product packaging. The research was conducted at PT Satyamitra Kemas Lestari using a quantitative approach, with descriptive methods, Pearson Product Moment correlation, and argumentative analysis. The results showed that digital proof improved color accuracy (ΔE < 3), maintained visual sharpness, and reduced printing errors. A significant correlation (r = 0.848) was found between digital proof quality and final print output. Thus, digital proofing should be adopted as a standard prepress procedure in the packaging industry.